2010
DOI: 10.1111/j.1365-2249.2010.04275.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal country of origin, breast milk characteristics and potential influences on immunity in offspring

Abstract: SummaryBreast milk contains pro-and anti-inflammatory cytokines and chemokines with potential to influence immunological maturation in the child. We have shown previously that country of birth is associated with the cytokine/ chemokine profile of breast milk. In this study we have investigated how these differences in breast milk affect the cellular response of cord blood mononuclear cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
2
40
1
Order By: Relevance
“…We also observed variation in EGF as a negative function of infant age ( Figure 4B), a result that agrees well with earlier studies (Donovan and Odle 1994). Perhaps importantly, we observed relatively elevated levels of TGF-β 2 in the milk of Aeta women, suggesting a greater exposure to infectious pathogens (Amoudruz et al 2009;Peroni et al 2010); however, median levels in Aeta and Ilocano milks (2,419 and 1,644 pg/ml, respectively) were lower than mean values from Mali (3,727 pg/ml) and Sweden (3,703 pg/ml) (Holmlund et al 2010). Such a difference highlights the potential for global variation in the baseline values of some cytokines (McDade et al 2009).…”
Section: Discussionsupporting
confidence: 79%
“…We also observed variation in EGF as a negative function of infant age ( Figure 4B), a result that agrees well with earlier studies (Donovan and Odle 1994). Perhaps importantly, we observed relatively elevated levels of TGF-β 2 in the milk of Aeta women, suggesting a greater exposure to infectious pathogens (Amoudruz et al 2009;Peroni et al 2010); however, median levels in Aeta and Ilocano milks (2,419 and 1,644 pg/ml, respectively) were lower than mean values from Mali (3,727 pg/ml) and Sweden (3,703 pg/ml) (Holmlund et al 2010). Such a difference highlights the potential for global variation in the baseline values of some cytokines (McDade et al 2009).…”
Section: Discussionsupporting
confidence: 79%
“…Our study indicates that whey from African-American mothers had increased levels of IL-6, IFN-γ, and CXCL8 compared with those of other racial/ethnic groups ( Table 5). Recently, Holmlund et al found that breast milk of women who immigrated to Sweden contained higher levels of TGF-β1 and CXCL8 than milk from native Swedish women (27). Country of origin seems to play a role in the concentration of CXCL8 and TGF-β1 in breast milk, which further supports the idea that race/ethnicity may influence whey cytokine levels.…”
Section: Maternal Characteristics and Other Child's Covariatesmentioning
confidence: 88%
“…TGF-β1 (30, 31, 35, 50, 68, 72, 75-77, 80, 81, 83, 122, 127, 131, 137, 148, 149, 152, 153) TGF-β2 (30,31,35,50,52,68,72,73,75,77,80,122,125,127,152) TGF-β3 (35) EGF (122) HGF (49,154) inhibitors CST3 (46,47) SERPIN-A1, A3, B1, C1, G1 (46,47) SPINT1 (46,47) Other Coenzyme A (157) β-casomorphin (158) sCD14 (8,31,72,75,77,83,131,148,153) Other factors did not differ. …”
Section: Growth Factorsmentioning
confidence: 99%